Interpersonal Communication of Employees in Services for the Elderly with Cognitive Impairments in the Harapan Kita Elderly Social Home - Sakinah; Budianto; Chairunnisah Putri Ayu Ningsih (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This research is motivated by the importance of interpersonal communication in services for the elderly who experience cognitive impairment, such as memory loss, difficulty understanding instructions, emotional changes, and slow communication responses. This condition requires employees to be able to adjust the way they communicate so that the services provided remain effective and able to create a sense of comfort for the elderly. This study aims to find out how employee interpersonal communication in services for the elderly with cognitive impairment and to find out the obstacles faced by employees in the communication process. This study uses a qualitative descriptive method with data collection techniques through observation, in-depth interviews, and documentation. The research informants consisted of employees and the elderly at the Harapan Kita Indralaya Elderly Social Home. The theory used in this study is Interaction Adaptation Theory by Judee K. Burgoon which explains that individuals will adjust their communication behavior based on the needs and conditions of the interlocutor in an interaction.